Job stress and its determinants among academic staff in a university in Klang Valley, Malaysia - Muhamad Zaki, Nor Amalina; Zainuddin, Huda; Abdul Rahman, Hejar (Community Health Society Malaysia, 2016)
Background: Job stress is the most common condition experienced by workers which occurs when there is a conflict between the workplace, workload and individual’s ability to cope with the situation (Ongori & Agolla, 2008). Stress is an event that occurs when the body is upset and unbalanced. It is caused by stressors in term of environmental condition and on how is the person react and response towards the challenging events. Job stress is the most common condition experienced by workers which occurs due to various socio demographic and work factors. This study aimed to determine job stress and its determinants among academic staff at Universiti Putra Malaysia, Serdang, Malaysia. Materials and Methods: A cross-sectional study was done on academic staff in Universiti Putra Malaysia, Serdang. Workplace Stress Questionnaire was used to assess the stress level while NIOSH Generic Job Stress Questionnaire was used to assess factors affecting job stress among the academic staff at Universiti Putra Malaysia. Binary logistic regression analysis was conducted to identify the determinants of job stress among the respondents. Result: Of 421 respondents, 60.8% of respondents were experienced job stress. Most (54.6%) of the academic staffs experienced moderate stress and 2.6% of them were experienced severe stress due to their job. This study has found that hours of work, (45 to 60 hours per week, AOR = 2.339, 95% CI = 1.287 - 4.253; >60 hours per week, AOR = 1.174, 95% CI = 0.680 - 2.029) and workload and responsibility at workplace (AOR = 1.190; 95% CI = 1.098 - 1.291) are the determinants of job stress among the academic staff at Universiti Putra Malaysia. Conclusion: Prolonged hours of working and high workload and responsibility determine job stress status among academic staff. It is recommended that the management of the university plan and implement job stress prevention and management programs emphasizing on time management and working strategies to improve the situation. Cohort studies that include other variables not covered in this research are recommended for more conclusive findings and to establish the causes of job stress among academics.